High Lifetime Ga‐Doped Cz‐Si for Carrier‐Selective Junction Solar Cells. Issue 8 (12th August 2022) - Horzel, Jörg; Mack, Sebastian; Voicu Vulcanean, Ioan; Zimmermann, Karin; Pingel, Sebastian; Kwapil, Wolfram; Maischner, Felix; Höffler, Hannes; Bashardoust, Sattar; Wagenmann, Dirk; Greulich, Johannes; Seif, Johannes; et al.
Abstract : Industrial mass production of solar cells is at a transition toward carrier‐selective junction solar cells with passivating contacts such as TOPCon, POLO, or heterojunction technology (HJT). At the same time, many manufacturers consider switching from p‐type Cz‐Si to n‐type Cz‐Si wafers. This contribution indicates that Ga‐doped p‐type Cz‐Si material is still a viable option for the new type of devices while giving an opportunity to benefit from lower wafer cost. The minority carrier diffusion lengths that are an order of magnitude larger than the thickness of the studied HJT and TOPCoRE devices are reported. Stability aspects for operation in the field are discussed. Best TOPCoRE solar cells on Ga‐doped Cz‐Si show a 0.2% higher efficiency than their co‐processed n‐type counterparts. Abstract : Ga‐doped Cz‐Si material has been systematically analyzed with respect to its performance in high‐efficiency solar cells with carrier selective junctions applying high‐temperature TOPCon and low‐temperature heterojunction processing. Ga‐doped Cz‐Si is due to its lower wafer cost and good performance an economically beneficial alternative to n‐type wafer material.